Retraction Note: Exploring the molecular mechanisms of rice blast resistance and advances in breeding for disease tolerance - Muhammad Usama Younas; Muhammad Qasim; Irshad Ahmad; Zhiming Feng; Rashid Iqbal; Xiaohong Jiang; Shimin Zuo (Molecular Biology Reports, 2026)

Artificial photosynthesis of H2O2 with covalent organic frameworks: From structural design to catalytic function - Ajmal Khan; Yasser A. Alassmy; Mohammed Qasem Alfaifi; Marwan M. Abduljawad; Sultan A. Alshuhri; Irshad Ahmad; Qinyun Huang; Yuyu Liu; Muhammad Arshad (Journal of Environmental Chemical Engineering, 2026)

Defect engineering of complex perovskite oxide via plasmonic metal (La0.6Sr0.4Fe0.7Cu0.1Co0.2O3) in polymeric network hydrogel for enhanced solar steam generation - Naila Arshad; Muhammad Sultan Irshad; Lamia Abu El Maati; Afraa Alotaibi; Van-Duong Dao; Naveed Mushtaq; Muneerah Alomar (Journal of Environmental Chemical Engineering, 2026)

Reusing end-of-life reverse osmosis membranes: Strategies, challenges, and future perspectives - Zeeshan Arshad; Muhammad Ashraf; Taha Demraoui; Tauqir Ahmad; Muhammad Bilal Asif; Niaz Ali Khan; Mukarram Zubair; Muhammad Irshad Baig; Nisar Ullah; Yasir Abbas; Almotasembellah Abushaban; Nadeem Baig (Desalination, 2026)

Hydrogenation of CO2 to formate/formic acid over Pd/H-MOR - Faisal Irshad; Dan Zhang; Hamzah A.S.M. Yaseen; Xianming Zhu; Muhammad Chawla; Shengping Wang; Yongli Shen; Xinbin Ma (Chemical Engineering Journal, 2026)

Retraction Note: Matrine alleviates neurobehavioral alterations via modulation of JNK-mediated caspase-3 and BDNF/VEGF signaling in a mouse model of burn injury - Adnan Khan; Bushra Shal; Muhammad Naveed; Bakht Nasir; Nadeem Irshad; Hussain Ali; Salman Khan (Psychopharmacology, 2026)

Retraction notice to “A critical review of mercury speciation, bioavailability, toxicity and detoxification in soil-plant environment: Ecotoxicology and health risk assessment” [Sci. Total Environ. 711 (2020) 134749] - Natasha; Muhammad Shahid; Sana Khalid; Irshad Bibi; Jochen Bundschuh; Nabeel Khan Niazi; Camille Dumat (Science of The Total Environment, 2026)

Reusable composite adsorbent for aqueous solutions and soils multi-contaminated with As(V), Cd(II), Pb(II), and diesel - Jong Cheol Lee; Hailu Fu; Muhammad Kashif Irshad; Hun Ho Lee; Dong Hwan Shin; Sang Soo Lee (Journal of Water Process Engineering, 2026)

An analysis of impact of soil co-pollution with lead and traditional/biodegradable microplastics on growth characteristics of maize (Zea mays L.) - Muhammad Kashif Irshad; Saba Saleem; Jamilur R. Ansari; Ali Noman; Muhammad Aqeel; Mohamed O. Alshahrani; Modhi O. Alotaibi; Muhammad Sohaib Irshad; Sang Soo Lee (Journal of Environmental Sciences, 2026)

Aqueous phase separation membranes: Fundamentals, mechanisms, and emerging green fabrication strategies - Tausif Ahmad; Abdullah Sani; Muhammad Irshad Baig (Desalination, 2026)

Assessment of functional trait variation in arid-zone plant families to evaluate indicator species for rehabilitation of degraded landscapes - Eisha Kanwal; Farooq Ahmad; Ansa Asghar; Ummar Iqbal; Anum Javaid; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Saba Gul; Muhammad Irshad; Khawaja Shafique Ahmad (The Science of Nature, 2026)

Investigating Charge-Carrier Dynamics in Heteroatom-Functionalized Triphenylamine Hole Transport Materials for Perovskite Solar Cells - Faiza Iram; Zobia Irshad; Riaz Hussain; Muhammad Imran; Mahmood Ahmed; Muhammad Adnan; Jae Kwan Lee (Journal of Fluorescence, 2026)

Melatonin Buffers Microplastic-induced Oxidative Stress in Rice by Restoring Redox Balance, Antioxidants Reprogramming and Phytohormone Homeostasis - Ali Noman; Osman Sonmez; Noreen Khalid; Muhammad Kashif Irshad; Afrah E. Mohammed; Modhi O. Alotaibi; Muhammad Aqeel (Journal of Soil Science and Plant Nutrition, 2026)

Comparative in vitro pathogenicity of different oil-based formulations of Metarhizium anisopliae against three different aphid species - Ahmad Nawaz; Anam Ejaz; Tariq Mustafa; Usman Naeem; Amna Irshad; Muhammad Dildar Gogi; Muhammad Tayyib; Muhammad Naveed; Amjad Abbas; Muhammad Jalal Arif (International Journal of Tropical Insect Science, 2026)

Tailoring SrFeO3-δ cathodes via Nd and Cu doping for boosting ORR activity for high-performance LT-PCFCs below 600 °C - Naveed Mushtaq; Wu Ping; Badriah S. Almutairi; Sajid Rauf; M.A.K Yousaf Shah; Muhammad Sultan Irshad (Fuel, 2026)

Correction to: Diversity of wild Morchella (Ascomycota) revealed by integrated morphological and molecular analyses - Sania Shoukat; Nasir Mehmood; Salman Ghuffar; Sadiqa Bibi; Muhammad Rauf; Gulshan Irshad; Gule-e-Lalah Khan; Sumaira Maqsood; Tauseef Anwar; Huma Qureshi; Nazih Y. Rebouh; Salohiddinjon Yunusov; et al. (Folia Microbiologica, 2026)

Clinical evaluation of adjunctive magnesium therapy in patients receiving antidepressants for depression—open label, nonrandomized clinical trial - Afifa Siddique; Uzma Naeem; Muhammad Masood Khokhar; Mushayada Irshad; Tayaba Farooq; Sughra Kanwal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Parametric optimization and mechanistic investigation of polyvinyl chloride microplastic degradation via an intensified hydrothermal Fenton reaction - Muhammad Zeeshan Gulzar; Guijian Liu; Muhammad Imran; Muhammad Arif; Samina Irshad; Bisma Sattar; Muhammad Irtaza Sajjad Haider; Huihui Zhou; Balal Yousaf (Journal of Water Process Engineering, 2026)

A V-shaped CNT-decorated LiNi0.8Co0.15Al0.05O2 photothermal fabric for high-efficiency solar steam generation and desalination - Huibin Guan; Naila Arshad; Bushra Shakoor; Najah Alwadie; Xiaochao Fan; Ruijing Shi; Van-Duong Dao; Nang Xuan Ho; Jian Zhang; Muhammad Sultan Irshad; Calvyn T. Howells; Phuong Anh Lam; et al. (Journal of Environmental Chemical Engineering, 2026)

The role of MXene interfaces in decoupling electronic and thermal transport in Bi2Te3 composites - Samira Saddique; Inaam Ullah; Syed Zuhair Abbas Shah; Ayesha Irfan; Nimra Irshad; Muhammad Irfan; Shanza Taswar; Salamat Ali; Muhammad Amer Mustafa; Guiying Xu (Chemical Engineering Journal, 2026)

Synergistic Degradation and Cytotoxicity Mitigation of Meloxicam Using UV/Perovskite/H₂O₂ and Gamma/H₂O₂: A Comparative Study - Muhammad Asad Khan; Mohamed A. Habib; Muhammad Imran Kanjal; Majid Muneer; Muhammad Asghar Jamal; Tanveer Hussain Bokhari; Usman Irshad; Ahmed B. M. Ibrahim (Water, Air, & Soil Pollution, 2026)

Retraction notice to ‘Morpho-chemical characterization and source apportionment of potentially toxic metal(oid)s from school dust of second largest populous city of Pakistan’ [Environ. Res. 196 (2021) 110427] - Abdul Rehman; Guijian Liu; Balal Yousaf; Rafay Ahmed; Muhammad Saqib Rashid; Samina Irshad; Awais Shakoor; Muhammad Raza Farooq (Environmental Research, 2026)

The interaction between energy transition, pollution, recycling, and ecological footprint: Lessons from European countries - José Alberto Fuinhas; Zakir Khan; Matheus Koengkan; Hussain Muhammad Irshad; Hélde Domingos (Energy Policy, 2026)

Gastroprotective effect of Kahweol against ethanol-induced gastric ulcer by employing in silico, in vitro and in vivo approaches - Shahid Khan; Abdul Qadir; Jawad Azam; Muhammad Noman; Nadeem Ahmad; Zaheer Ul-Haq; Kashif Bashir; Tajamul Hussain; Salman Alrokayan; Muhammad Latif; Hussain Ali; Yousaf Kamal; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Spatial distribution of heavy metals and ecological risk assessment in Sea buckthorn across high-mountain landscapes of HKH ranges, Gilgit-Baltistan, Pakistan - Kamran Ali Khan; Faridullah Faridullah; Adnan Ahmad Tahir; Muhammad Irshad; Shaxina Tuyg’unovna Shukurova; Farhan Hafeez; Arshad Mahmood Abbasi (Environmental Geochemistry and Health, 2026)

Diversity of wild Morchella (Ascomycota) revealed by integrated morphological and molecular analyses - Sania Shoukat; Nasir Mehmood; Salman Ghuffar; Sadiqa Bibi; Muhammad Rauf; Gulshan Irshad; Gule-e-Lalah Khan; Sumaira Maqsood; Tauseef Anwar; Huma Qureshi; Nazih Y. Rebouh; Salohiddinjon Yunusov; et al. (Folia Microbiologica, 2026)

Advances in green food processing technologies: Enhancing efficiency, safety, and sustainability - Asad Nawaz; Sana Irshad; Xiaofang Luo; Noman Walayat; Putri Widyanti Harlina; Zuodong Qin; Muhammad Afzaal; Fakhar Islam (Food Control, 2026)

Arginine-Dependent Defense Actions in Rice (Oryza Sativa L.) Against Microplastic Contaminated Root Zone - Modhi O. Alotaibi; Naila Hadayat; Mohamed O. Alshahrani; Muhammad Kashif Irshad; Anees Manzoor; Nahaa M. Alotaibi; Fahad Mohammed Alzuaibr; Suliman Mohammed Suliman Alghanem; Omar Mahmoud Alzoubi; Jeddi Kaouthar; Saher Nawaz (Journal of Soil Science and Plant Nutrition, 2026)

Alleviation of Lead Stress in Maize Plants Through the Application of Green-Synthesized Zinc Oxide Nanoparticles - Haseeba Maryam; Nasir Masood; Muhammad Waseem; Temoor Ahmed; Muhammad Zia-ur-Rehman; Muhammad Atif Irshad; Saher Javed; Muhammad Rizwan (Journal of Soil Science and Plant Nutrition, 2026)

Synergistic NiO-Pt heterostructure for enhanced hydrogen evolution: Boosting charge transfer and catalytic efficiency in alkaline media - Faria Rafique; Shahzad Ameen; Muhammad Hammad Ali; Aleena Tahir; Hamayal Shahzad; Amina Bhatti; Tanveer ul Haq; Mira Tul Zubaida Butt; Ammar Ahmed Khan; Saleh A. Ahmed; Irshad Hussain; Habib Ur Rehman (Fuel, 2026)

Effects of Melatonin on Morpho-Physiological Activity of Cotton Seedlings Under Cold and Normal Temperature - Irshad Ahmad; Guanglong Zhu; Xuebing Yan; Yanqing Wu; Muhammad Usama Younas; Guisheng Zhou (Journal of Plant Growth Regulation, 2026)

Projection-based molecular feature maps for CNN-driven nephrotoxicity prediction - Muhammad Zafar Irshad Khan; Jia-Nan Ren; Hong-Yu-Xiang Ye; Cheng Cao; Xiao-Bi Liu; Jian-Zhong Chen (Archives of Toxicology, 2026)

Synergistic effects of biochar and silicon dioxide nanoparticles abate cadmium uptake and oxidative stress in tomato: Achieving crop resilience and environmental sustainability - Muhammad Kashif Irshad; Muhammad Waseem; Saba Saleem; Jamilur R. Ansari; Sana Ashraf; Wasim Javed; Ali Noman; Muhammad Aqeel; Muhammad Rizwan; Afrah E. Mohammed; Modhi O. Alotaibi; Muhammad Rizwan; et al. (Plant Science, 2026)

Synergetic effect of SBR latex, silica fume and steel fibers on fresh and hardened properties of concrete with high density polyethylene plastic used in the form of aggregates - Syed Nasir Abbas; Muhammad Irshad Qureshi (Innovative Infrastructure Solutions, 2026)

Synergistic effects of selected ethnomedicinal plants with Metronidazole against resistant H. Pylori, and their urease inhibition mechanism - Sania Atta; Marya Nawaz Malik; Muhammad Tahir Aqeel; Iffat Naz; Nadeem Irshad; Sadaf Naz; Nadeem ul Hassan Khan; Faisal Rasheed; Humaira Fatima (South African Journal of Botany, 2025)

Structural and functional responses of Panicum antidotale to diverse ecohydrological conditions - Muhammad Irshad; Mansoor Hameed; Farooq Ahmad; Ummar Iqbal; Jazab Shafqat; Ansa Asghar (Ecohydrology & Hydrobiology, 2025)

Genetic Mechanisms and Improvement Strategies for Rice Sheath Blight Resistance - Muhammad Usama Younas; Bisma Rao; Muhammad Qasim; Irshad Ahmad; Zhiming Feng; Saima Parveen Memon; Rashid Iqbal; Shimin Zuo (Plant Molecular Biology Reporter, 2025)

Improving Nitrogen Efficiency and Photosynthesis in Wheat Using integrated Nitrogen Management and Modified Geometry - Uzair Ahmed; Muhammad Waseem Abbas; Jalal Bayar; Irshad Ali Khan; Aneela Tahmeed; Muhammad Mehran Anjum; Nawab Ali; Gul Roz Khan; Hazrat Usman; Mahmoud F. Seleiman (Journal of Soil Science and Plant Nutrition, 2025)

Effect of Fagonia Indica and Garlic Extract On Alternaria Alternata and Post-harvest Quality of Tomato Fruit During Storage - Sameer Lal; Ghulam Khaliq; Abdul Hafeez Mastoi; Asif Irshad; Muhammad Abuzar Jaffar; Lawang Khan; Noor Muhammad (Journal of Crop Health, 2025)

An Inclusive Approach to Disaster Risk Reduction in Water-Related Hazards for the Mining Industry: Prioritizing the Multi-Dimensional Risk Framework for Achieving Sustainable Development - Aboubakar Siddique; Zhuoying Tan; Jiang Li; Asaad Algarni; Irshad Ali Zardari; Muhammad Zeshan; Saddam Hussain Khurram; Dhanesh Kumar (Mine Water and the Environment, 2025)

Morpho-molecular diversity and host range dynamics of squash powdery mildew pathogens prevailing in Pothwar Plateau, Pakistan - Beenish Gul; Farah Naz; Mathews L. Paret; Fanny Iriarte; Zain Haider; Gulshan Irshad; Muhammad Azam Khan (Journal of Plant Pathology, 2025)

Side structural regulation strategy of 3D gear evaporators for enhanced solar water evaporation and salt harvesting - Junyang Tao; Zihan Feng; Shan Zhai; Suji Huang; Yi E; Fengshuai Zhu; Liangyou Lin; Jingwen Qian; Muhammad Sultan Irshad; Xianbao Wang (Desalination, 2025)

Beyond brine: Super salt-resistant solar evaporator via inclined brine regulation and sustainable energy transition - Yuchen Gan; Zihan Feng; Ruilei Xiao; Muneerah Alomar; Dang Viet Quang; Nang Xuan Ho; Naila Arshad; Junyang Tao; Saif Ur Rehman; Xianbao Wang; Van-Duong Dao; Muhammad Sultan Irshad (Desalination, 2025)

3D arched solar evaporator with latent heat recovery for high-performance seawater desalination and sustainable saline agriculture - Yi E; Naila Arshad; Zhengguo Jiao; Junyang Tao; Jingwen Qian; Tao Mei; Muhammad Sultan Irshad; Xianbao Wang (Desalination, 2025)

Recent advances in conducting polymers for hybrid solar-driven evaporation systems: Fundamentals, innovations, and applications - Bushra Shakoor; Muhammad Sultan Irshad; Uzma Ghazanfar; Humaira Razzaq; Naila Arshad; Ghazala Maqsood; Iftikhar Ahmed; Muhammad Atif Ali; Muhammad Sohail Asghar; Irshad Hussain; Tao Mei; Tran Vinh Dieu; et al. (Chemical Engineering Journal, 2025)

NiMn-LDH/polypyrrole photothermal structures for interfacial solar steam generation - Ghazala Maqsood; Muhammad Sohail Asghar; Bushra Shakoor; Muneerah Alomar; Muhammad Atif Ali; Yi E; Tao Mei; Muhammad Sultan Irshad; Xianbao Wang (Chemical Engineering Journal, 2025)

Modulating condensate efficiency with hybrid solar evaporation: Synergistic photothermal and joule heating for high-performance water harvesting - Yi E; Naila Arshad; Zhengguo Jiao; Junyang Tao; Muneerah Alomar; Jingwen Qian; Tao Mei; Nang Xuan Ho; Van-Duong Dao; Muhammad Sultan Irshad; Xianbao Wang (Chemical Engineering Journal, 2025)

Nanogel-based delivery of dequalinium chloride: A novel approach for antimicrobial and controlled drug release - Ammara Sayyeda; Zulcaif Ahmad; Syeda Momna Ishtiaq; Asma Irshad; Saniia Shchinar; Muhammad Farhan Sohail (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Retraction Note: The nexus between urbanization, renewable energy consumption, financial development, and CO2 emissions: evidence from selected Asian countries - Ahsan Anwar; Avik Sinha; Arshian Sharif; Muhammad Siddique; Shoaib Irshad; Waseem Anwar; Summaira Malik (Environment, Development and Sustainability, 2025)

Highly efficient and durable solar-driven desalination using MoS2 aerogels enabled by PEG-induced hydration modulation - Jiameng Zhang; Zhenzhen Guo; Haoran Zhang; Tianxiang Zhou; Muneerah Alomar; Xiaochao Fan; Uzma Ghazanfar; Phan Thi Dien; Bui Thi My Duyen; Muhammad Sultan Irshad; Van-Duong Dao (Journal of Environmental Chemical Engineering, 2025)

Tailoring polymerized fabrics for sustainable water-driven electricity and salt-water separation membrane - Zhenzhen Guo; Jiameng Zhang; Haoran Zhang; Wanqing Zhang; Naila Arshad; Muneerah Alomar; Nang Xuan Ho; Xiaochao Fan; Muhammad Sultan Irshad; Van-Duong Dao; Xianbao Wang (Desalination, 2025)

Clean water and energy co-generation via alternative renewables - Xiaochao Fan; Bushra Shakoor; Han Yusen; Shi Ruijing; Yang Mingtao; Li Ziqiang; Naila Arshad; Uzma Ghazanfar; Van-Duong Dao; Jian Zhang; Muhammad Sultan Irshad; Calvyn T. Howells; et al. (Chemical Engineering Journal, 2025)

Role of Na in promoting n-butanol production via CO2 hydrogenation over a Cu-Co catalyst - Muhammad Irshad; Heuntae Jo; Syeda Sidra Bibi; Seok Ki Kim; Hee-Joon Chun; Jaehoon Kim (Chemical Engineering Journal, 2025)

Integrated Approaches for Enhancing Magnaporthe oryzae Resistance: Mechanisms and Breeding Strategies - Muhammad Usama Younas; Muhammad Qasim; Irshad Ahmad; Zhiming Feng; Rashid Iqbal; Tanweer Fatah Abro; Shabir Ahmad; Xiaohong Jiang; Nimra Rajput; Shimin Zuo (Plant Molecular Biology Reporter, 2025)

Correction to: Evaluation of the perception of climate change and its implications across various geo-physical regions of Kashmir Himalayas - Hilal Ahmad Parrey; Mohammad Shafi Bhat; Shamim Ahmad Shah; Mir Sumira; Irshad Ahmad Thoker; Muhammad Mubashar Dogar; Sanju Purohit; Muhammad Ahmad Dogar; Maria Anwar (Natural Hazards, 2025)

Evaluation of the perception of climate change and its implications across various geo-physical regions of Kashmir Himalayas - Hilal Ahmad Parrey; Mohammad Shafi Bhat; Shamim Ahmad Shah; Mir Sumira; Irshad Ahmad Thoker; Muhammad Mubashar Dogar; Sanju Purohit; Muhammad Ahmad Dogar; Maria Anwar (Natural Hazards, 2025)

Endophytic Meyerozyma guilliermondii augmented growth attributes and metabolite production in Triticum aestivum under salinity stress - Zeeshan Khan; Muhammad Irshad; Anwar Hussain; Arshad Iqbal; Zamarud Shah; Waheed Murad; Eman R. Elsharkawy; Muhammad Nafees (Folia Microbiologica, 2025)

Functionalized carbon nanotubes interconnected with metal-organic frameworks for in-situ solar-driven evaporation and salt recovery from seawater - Muhammad Sohail Asghar; Muhammad Sultan Irshad; Naila Arshad; Maryam Al Huwayz; Muneerah Alomar; Ghazala Maqsood; Muhammad Atif Ali; Uzma Ghanzanfar; Muhammad Sabir; Jinhua Li; Van-Duong Dao; Nang Xuan Ho; et al. (Water Research, 2025)

Association of microplastics with lead and cadmium in soil: Land-use and temporal trends - Noreen Khalid; Muhammad Aqeel; Shiou Yih Lee; Ujala Ejaz; Ali Noman; Muhammad Faisal Maqsood; Muhammad Kashif Irshad; Mohamed A. El-Sheikh (Journal of Environmental Chemical Engineering, 2025)

Synthesis of selective C5+ paraffins directly from CO2 over Cu-Co catalyst: Dynamic role of Cu to establish the Fischer–Tropsch synthesis process - Muhammad Irshad; Heauntae Jo; Syeda Sidra Bibi; Jaehoon Kim (Chemical Engineering Journal, 2025)

Molecular identification, risk factors’ assessment and phylogenetic analysis of Toxoplasma gondii in goats from Malakand Division, Khyber Pakhtunkhwa, Pakistan - Ahmad Irshad; Shumaila Noreen; Uswa Sajid; Muhsin Jamal; Muhammad Anwar Iqbal; Ubaid Ullah; Talat Sabtain; Shakir Ullah; Eliana Ibañez-Arancibia; Patricio R. De Los Ríos-Escalante; Hanène Belkahia; Mourad Ben Said; et al. (Veterinary Research Communications, 2025)

Impact of bagasse ash on workability, splitting tensile strength and flexural strength properties of concrete - Syed Nasir Abbas; Muhammad Irshad Qureshi (Innovative Infrastructure Solutions, 2025)

Spatial distribution of potentially toxic elements and ecological-health risks in a wastewater-irrigated peri-urban agroecosystem: a multi-matrix assessment from Muzaffargarh, Pakistan - Muhammad Tansar Abbas; Jalal Uddin; Irshad Ullah; Abd Ullah; Hidayat Ullah; Abdullatif Bin Muhsinah; Syed Ghulam Musharraf; Pankaj Kumar (Environmental Geochemistry and Health, 2025)

Probing the synergistic effect of MXene (TiCT) and MWCNTs on NiWO for superior water-splitting and supercapacitor studies - Amna Irshad; Mirza Mahmood Baig; Seung Goo Lee; Imran Shakir; Zeid A. ALOthman; Muhammad Farooq Warsi; Muhammad Shahid (Fuel, 2025)

How does commercial energy impact Pakistan’s environmental quality? The case of the agricultural, industrial and transportation industries - Abdul Rehman; Zakia Batool; Qurat ul Ain; Ruifeng Liu; Muhammad Irshad Ahmad; Hengyun Ma; Ilhan Ozturk (Environment, Development and Sustainability, 2025)

Importance of an Oncology Interest Group in Medical School: Experience from a Developing Country - Hammad Atif Irshad; Abdul Rehman; Muhammad Ali Akbar Khan; Dahir Ashfaq; Munira Moosajee (Journal of Cancer Education, 2025)

Variation in mechanical properties of concrete having recycled brick aggregates, recycled concrete aggregates and recycled plastic aggregates: A review - Syed Nasir Abbas; Muhammad Irshad Qureshi (Next Research, 2025)

Urban flood management from the lens of social media data using machine learning algorithms - Muhammad Waseem Boota; Shan-e-hyder Soomro; Jikun Xu; Muhammad Irshad Ahmad; Haoming Xia; Yaochen Qin; Muhammad Bilal Idrees; Naseem Ahmad; Chaode Yan; Ayesha Yousaf; Xiaoju Ning (Journal of Hydrology, 2025)

Microplastic Contaminated Root Zone Supplementation With Ascorbic Acid Enhance Photosynthesis, Antioxidant Defense, ROS Scavenging, and Secondary Metabolites in Rice - Khairiah Mubarak Alwutayd; Muhammad Aqeel; Noreen Khalid; Saher Nawaz; Noreen Akhter; Muhammad Kashif Irshad; Uthman Bagith Algopishi; Suliman Mohammed Suliman Alghanem; Ali Noman (Journal of Soil Science and Plant Nutrition, 2025)

E-waste in concrete construction: recycling, applications, and impact on mechanical, durability, and thermal properties—a review - Farhan Ahmad; Muhammad Irshad Qureshi; S. Rawat; Mohammed K. Alkharisi; Mansour Alturki (Innovative Infrastructure Solutions, 2025)
The exponential growth in industrialization, urbanization, and population has subsequently increased the accumulation of different wastes to hazardous levels. Among these, electronic waste (E-waste) poses a serious threat to the environment with its production rising due to technological advancements worldwide. Therefore, recycling E-waste as an alternate aggregate replacement material in the construction industry can be advantageous in managing this waste stream. This study aims to present a comprehensive insight into the integrated applications of E-waste concrete composite materials in the construction industry including applications to increase the environmental sustainability of concrete structures. This review starts with an illustration of the environmental issues caused by E-waste, elucidates its sources and prevailing recycling practices, and investigates its utility as supplementary cementitious materials. This discussion is further followed by an analysis on recycled E-waste plastic aggregate concrete (RPAC) composites, covering their fresh properties, mechanical properties, thermal properties, durability, and serviceability performance. Besides, this paper also explores the evaluation of the utilization of E-waste fibers (E-fiber) as well as the application of E-waste glass (E-glass) from cathode ray tubes (CRT) in concrete. Based on the detailed review, the positive aspects and the restrictions associated with utilizing E-waste in construction have been highlighted.

Exploring the hidden world of muskmelon miRNAs: experimental hunts of computational predicted miRNAs and their protein targets - Abdul Ghaffar; Naqeebullah Khan; Irshad Ali; Attiq ur Rehman; Samiullah; Waheed Ahmed Shah; Muhammad Javed Khan (Genetic Resources and Crop Evolution, 2025)

Identification and Characterization of Evolutionary Conserved Muskmelon Non-coding miRNAs and Their Target Proteins - Abdul Ghaffar; Naqeebullah khan; Muhammad Zafar Saleem; Irshad Ali; Attiq Ur Rehman; Waheed Ahmed Shah; Samiullah (Biochemical Genetics, 2025)

Scrutinizing the role of two distinct elicitors modulating light harvesting potential, specific energy fluxes and physiological tolerance in maize plants under sub-optimal environment - Zamin Shaheed Siddiqui; Komal Nida; Muhammad Umar; Zainul Abideen; Khadija Irshad; Jean Wan Hong Yong (South African Journal of Botany, 2025)

Trace element removal from wastewater by agricultural biowastes: A data analysis on removal efficacy and optimized conditions - Muhammad Shahid; Sana Khalid; Zeid A. ALOthman; Abdullah A. Al-Kahtani; Irshad Bibi; Rabia Naz; Natasha Natasha; Nabeel Khan Niazi; Jibran Iqbal; Changseok Han; Noor S. Shah; Behzad Murtaza (Science of The Total Environment, 2025)

Phytomining potential, micro-morphological assessment, and air pollution tolerance index of plant species in multi-metals contaminated soapstone and crushing stone mines - Tufail Shakeel; Ghulam Mujtaba Shah; Bibi Saima Zeb; Iram Gul; Muhammad Irshad; Habiba Zafar (Science of The Total Environment, 2025)

Asymmetric structure fabric-based energy manager for simultaneous power and steam generation - Zhenzhen Guo; Jiameng Zhang; Jichao Wang; Muneerah Alomar; Muhammad Sultan Irshad; Jinlong Wu; Chaoran Shi; Iftikhar Ahmed; Van-Duong Dao; Ruiqing Shi; Xiaochao Fan; Xianbao Wang (Desalination, 2025)

Metabolic dynamics and health risk assessment of heavy metal accumulation in urban–rural interface vegetable systems - Hidayat Ullah; Jalal Uddin; Muhammad Ijaz; Muhammad Haziq; Abdullatif Bin Muhsinah; Irshad Ullah; Mubashir Jamal (Environmental Monitoring and Assessment, 2025)

Safety assessment of novel oxadiazole derivatives in acute and sub-acute toxicity studies - Syeda Rida Zainab; Jehan Zeb Khan; Humaira Nadeem; Muhammad Khalid Tipu; Nadeem Irshad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Isolation and characterization of Aspergillus oryzae from Withania coagulans rhizosphere: metabolite profiling and bioactivity assessment - Sidra Farooq; Asif Mehmood; Nasir Ali; Muhammad Irshad; Anwar Hussain; Naeem Khan (Journal of Plant Biochemistry and Biotechnology, 2025)

Assessing the Influence of Potassium Fertilizer Variations on Growth, Yield, and Crop Quality of Sugarcane (Saccharum officinarum L.) Genotypes - Wajid Ali Hisbani; Bonface O. Manono; Muhammad Nawaz; Kashf Mehmood; Zuhair Hasnain; Afroz Rais; Sohail Irshad; Danish Ibrar; Manzer H. Siddiqui; Saud Alamri; Shahbaz Khan (International Journal of Plant Production, 2025)

Morphology and multigene phylogeny revealed four new species of Agaricus section Minores from Pakistan - Rab Nawaz; Waheed Murad; Muhammad Irshad; Hira Bashir; Shah Hussain (Mycological Progress, 2025)

Graphene-Based Multi-Nanocomposites: Synthesis, Characterization and Photodegradation Analysis - Adeeba Sadia; Muhammad Irshad; Muhammad Faran Akhtar; Shaukat Ali; Muhammad Summer (Journal of Fluorescence, 2025)

Pyocins and Beyond: Exploring the World of Bacteriocins in Pseudomonas aeruginosa - Muhammad Suleman; Allah Rakha Yaseen; Shahbaz Ahmed; Zoha Khan; Asma Irshad; Afsah Pervaiz; Hafiza Hiba Rahman; Muteeba Azhar (Probiotics and Antimicrobial Proteins, 2025)

Jellyfish–mimetic solar evaporator with polyelectrolyte skeleton for sustainable desalination under higher salinity - Shan Zhai; Fang Yu; Naila Arshad; Suji Huang; Junyang Tao; Changwen Li; Liangyou Lin; Jingwen Qian; Muhammad Sultan Irshad; Xianbao Wang (Desalination, 2025)

Climate change projections for Diamer Division in lesser Himalayas using multi-global climate model ensemble - Didar Ahmad; Faridullah Faridullah; Muhammad Irshad; Aziz Ur Rahim Bacha; Farhan Hafeez; Akhtar Iqbal; Zahid Ullah; Muhammad Naveed Afridi; Abdulwahed Fahad Alrefaei; Rashid Nazir (Environmental Science and Pollution Research, 2024)

A study on the performance of enhancing environmental protection from molecular iodine using granular impregnated activated carbon - Talhat Yaqoob; Masroor Ahmad; Attaullah Shah; Amjad Farooq; Farman Ali; Sahid Mehmood; Sidra Shaoor Kiani; Muhammad Asim Irshad; Azeem Bibi; Naseem Irfan (Environmental Science and Pollution Research, 2024)

Potential of iron oxide-modified biochar in simultaneous mitigation of lead and nickel toxicity in wheat (Triticum aestivum L.) - Tufail Shah; Muhammad Kashif Irshad; Wasim Javed; Mahshab Sheraz; Atif Muhmood; Ali Noman; Maryam M. Alomran; Sang Soo Lee; Jianying Shang (South African Journal of Botany, 2024)

Mechanistic insight into interactive effect of microplastics and arsenic on growth of rice (Oryza sativa L.) and soil health indicators - Muhammad Kashif Irshad; Muhammad Aqeel; Saba Saleem; Wasim Javed; Ali Noman; Min Woo Kang; Noreen Khalid; Sang Soo Lee (Science of The Total Environment, 2024)

RETRACTED ARTICLE: Exploring the molecular mechanisms of rice blast resistance and advances in breeding for disease tolerance - Muhammad Usama Younas; Muhammad Qasim; Irshad Ahmad; Zhiming Feng; Rashid Iqbal; Xiaohong Jiang; Shimin Zuo (Molecular Biology Reports, 2024)

Allelic variation in rice blast resistance: a pathway to sustainable disease management - Muhammad Usama Younas; Muhammad Qasim; Irshad Ahmad; Zhiming Feng; Rashid Iqbal; Ashraf M.M. Abdelbacki; Nimra Rajput; Xiaohong Jiang; Bisma Rao; Shimin Zuo (Molecular Biology Reports, 2024)

The genus Hymenagaricus: phylogeny, time divergence estimation, and the description of three new species from Pakistan - Rab Nawaz; Waheed Murad; Muhammad Irshad; Shah Hussain (Mycological Progress, 2024)

Application of zinc nanoparticles as seed priming agent improves growth and yield of wheat seedlings grown under salinity stress by enhanced antioxidants activities and gas exchange attributes - Sara Zafar; Shahbaz Khan; Danish Ibrar; Muhammad Kamran Khan; Zuhair Hasnain; Kashf Mehmood; Afroz Rais; Safia Gul; Sohail Irshad; Muhammad Nawaz (Cereal Research Communications, 2024)

FGTN: Fragment-based graph transformer network for predicting reproductive toxicity - Jia-Nan Ren; Qiang Chen; Hong-Yu-Xiang Ye; Cheng Cao; Ya-Min Guo; Jin-Rong Yang; Hao Wang; Muhammad Zafar Irshad Khan; Jian-Zhong Chen (Archives of Toxicology, 2024)

Spatial patterned solar evaporator for effective thermal management in enhanced solar-driven evaporation, and wastewater remediation - Naila Arshad; Muhammad Sohail Asghar; Muhammad Sultan Irshad; Najah Alwadie; Jinhua Li; M.A.K Yousaf Shah; Zhengbiao Ouyang; Hao Wang; Ho Xuan Nang; Van-Duong Dao; Xianbao Wang (Chemical Engineering Journal, 2024)

Structure-activity relationship and deactivation behavior of iron oxide during CO2 hydrogenation - Sheraz Ahmed; Wonjoong Yoon; Heuntae Jo; Muhammad Irshad; Muhammad Kashif Khan; Jaehoon Kim (Chemical Engineering Journal, 2024)

A fluid approach to cosmic-ray modified shocks - B. Ramzan; S.N.A. Qazi; Irshad Salarzai; Muhammad Tahir; Arshad M. Mirza; A. Rasheed; M. Jamil (Advances in Space Research, 2024)

Tailorable MBene aerogel with the lowest evaporation enthalpy for solar seawater desalination and wastewater purification - Junyang Tao; Naila Arshad; Muhammad Sultan Irshad; Muneerah Alomar; Fengshuai Zhu; Suji Huang; Shan Zhai; Van-Duong Dao; Xianbao Wang (Chemical Engineering Journal, 2024)

Efficacy of Fe-Mg-bimetallic biochar in stabilization of multiple heavy metals-contaminated soil and attenuation of toxicity in spinach (Spinacia oleracea L.) - Muhammad Kashif Irshad; Jong Cheol Lee; Muhammad Aqeel; Wasim Javed; Ali Noman; Su Shiung Lam; Ali El Naggar; Nabeel Khan Niazi; Hun Ho Lee; Muhammad Ibrahim; Sang Soo Lee (Chemosphere, 2024)

Spatiotemporal changes in LULC and associated impact on urban Heat Islands over Pakistan using geospatial techniques - Zubair Irshad; Mujtaba Hassan; Salman Akbar; Muhammad Farooq; Farrukh A. Chishtie (Urban Climate, 2024)

Appraisal of potentially toxic metals contamination in protein supplements for muscle growth: A chemometric approach and associated human health risks - Misbah Irshad; Mahmood Ahmed; Muhammad Ramzan; Mehreen Fatima; Fatima Aftab; Mudassar Sanaullah; Shaista Qamar; Zohaib Iftikhar; Tanveer A. Wani; Seema Zargar (Journal of Trace Elements in Medicine and Biology, 2024)

Role of alkali metal in maintaining iron integrity during direct CO2 hydrogenation - Wonjoong Yoon; Heuntae Jo; Sheraz Ahmed; Muhammad Kashif Khan; Muhammad Irshad; Jiyeon Lee; Syeda Sidra Bibi; Jaehoon Kim (Chemical Engineering Journal, 2024)

Energizing rural Pakistan through optimization of stand alone hybrid systems with techno-economic, multi-criteria decision and sensitivity analysis - Muhammad Zubair; Irshad Ullah; Abdulaziz Alanazi; Mohana Alanazi; Imad Hassan; Shayan Tariq Jan (Environment, Development and Sustainability, 2024)

Enhanced capacity of thiol-functionalized sugarcane bagasse and rice husk biochars for arsenite sorption in aqueous solutions - Israr Masood ul Hasan; Nabeel Khan Niazi; Irshad Bibi; Fazila Younas; Fahad Al-Misned; Muhammad Bilal Shakoor; Fawad Ali; Shazia Ilyas; Muhammad Mahroz Hussain; Jinli Qiao; Andreas Lüttge (Environmental Science and Pollution Research, 2024)
The utilization of biowastes for producing biochar to remove potentially toxic elements from water represents an important pathway for aquatic ecosystem decontamination. Here we explored the significance of thiol-functionalization on sugarcane bagasse biochar (Th/SCB–BC) and rice husk biochar (Th/RH–BC) to enhance arsenite (As(III)) removal capacity from water and compared their efficiency with both pristine biochars (SCB–BC and RH–BC). The maximum As(III) sorption was found on Th/SCB–BC and Th/RH–BC (2.88 and 2.51 mg g −1 , respectively) compared to the SCB–BC and RH–BC (1.51 and 1.40 mg g −1 ). Relatively, a greater percentage of As(III) removal was obtained with Th/SCB–BC and Th/RH–BC (92% and 83%, respectively) at a pH 7 compared to pristine SCB–BC and RH–BC (65% and 55%) at 6 mg L −1 initial As(III) concentration, 2 h contact time and 1 g L −1 sorbent dose. Langmuir ( R 2 = 0.99) isotherm and pseudo-second-order kinetic ( R 2 = 0.99) models provided the best fits to As(III) sorption data. Desorption experiments indicated that the regeneration ability of biochars decreased and it was in the order of Th/SCB–BC (88%) > Th/RH–BC (82%) > SCB–BC (77%) > RH–BC (69%) up to three sorption–desorption cycles. Fourier-transform infrared spectroscopy and X-ray photoelectron spectroscopy results demonstrated that the thiol (-S–H) functional groups were successfully grafted on the surface of two biochars and as such contributed to enhance As(III) removal from water. Spectroscopic data indicated that the surface functional moieties, such as -S–H, − OH, − COOH, and C = O were involved to increase As(III) sorption on thiol-functionalized biochars. This study highlights that thiol-grafting on both biochars, notably on SCB–BC, enhanced their ability to remove As(III) from water, which can be used as an effective technique for the treatment of As from drinking water. Graphical Abstract

Facilitated transport of ferrihydrite with phosphate under saturated flow conditions - Tufail Shah; Kang Zhao; Ai Chen; Atif Muhmood; Syed Atizaz Ali Shah; Muhammad Kashif Irshad; Yuji Arai; Jianying Shang (Journal of Contaminant Hydrology, 2024)

A Gamma-ray spectroscopy approach to evaluate clay mineral composition and depositional environment: A case study from the lower Goru Formation, Southern Indus Basin, Pakistan - Wakeel Hussain; Miao Luo; Muhammad Ali; Harith F. Al-Khafaji; Irshad Hussain; Mazahir Hussain; Salah Alshareef Alkfakey Ahmed; Obaidullah (Journal of Applied Geophysics, 2024)

An innovative perovskite oxide enabling improved efficiency for low-temperature ceramic electrochemical cells - Yuzheng Lu; M. A. K. Yousaf Shah; Naveed Mushtaq; Muhammad Yousaf; Nabeela Akbar; Naila Arshad; Sultan Irshad (Fuel, 2024)

A review of rare earth oxides-based photocatalysts: Design strategies and mechanisms - Chengping Zhang; Irshad Ahmad; Samia Ben Ahmed; Muhammad Danish Ali; Md Rezaul Karim; Hossein Bayahia; Mohammad Ahmad Khasawneh (Journal of Water Process Engineering, 2024)

Spatial variation in iodine content with relation to soil physicochemical properties in lower Himalayan region - Jawad Ali; Muhammad Mohiuddin; Xinfeng Wang; Zahid Hussain; Muhammad Irshad; Munir Zia; Rashid Pervez; Mohammad K. Okla; Shakeel Ahmad (Environmental Research, 2024)

Evaluation of Bacillus spp. as biocontrol agents against chili leaf spot caused by Xanthomonas vesicatoria - Sadia Aziz; Saleem Akhtar Jamshed; Tariq Mukhtar; Gulshan Irshad; Shahzada Sohail Ijaz; Muhammad Usman Raja (Journal of Plant Diseases and Protection, 2024)

Investigation of heavy metals uptake in root-shoot of native plant species adjoining wastewater channels - Sardar Khyzer Bashir; Muhammad Irshad; Aziz Ur Rahim Bacha; Ping An; Faridullah Faridullah; Zahid Ullah (Environmental Monitoring and Assessment, 2024)

Berberine ameliorates the progression of primary sclerosing cholangitis by activating farnesoid X receptor - Hassan Hameed; Nida Irshad; Muhammad Abrar Yousaf; Sidra Mumtaz; Imran Sohail (Cell Biochemistry and Biophysics, 2024)

In-silico functional and molecular phenotypic analysis of NFKBIE (V194A), and PADI4 (G55S, V82A,G112A) gene mutations in rheumatoid arthritis - Fazal Shan; Irshad Ahmad; Muhammad Ibrahim Rashid (Journal of Proteins and Proteomics, 2024)

Unveiling the detrimental effects of polylactic acid microplastics on rice seedlings and soil health - Muhammad Kashif Irshad; Min Woo Kang; Muhammad Aqeel; Wasim Javed; Ali Noman; Noreen Khalid; Sang Soo Lee (Chemosphere, 2024)

Hierarchical S-scheme heterojunction systems: A comprehensive review on outstanding photocatalysts - Huimin Han; Muhammad Raheel Khan; Irshad Ahmad; Ayman Al-Qattan; Ijaz Ali; Md Rezaul Karim; Hossein Bayahia; Farhat S. Khan; Zubair Ahmad; Saad Ullah (Journal of Water Process Engineering, 2024)

A fuzzy classification method based on rules learning for shaded and unshaded hotspot faults on photovoltaic modules - Junaid Ali Khan; Shengxue Tang; Borui Ji; Fahad Khan; Muhammad Adeel Khan; Usman Khan Khalil; Irshad Ullah (Journal of Cleaner Production, 2024)

Synergy of zero-dimensional carbon dots decoration on the one-dimensional architecture of Ag-doped V2O5 for supercapacitor and overall water-splitting applications - Amna Irshad; Sonia Zulfiqar; Zeid A.Alothman; Imran Shakir; Muhammad Farooq Warsi; Eric W. Cochran (Fuel, 2024)

Differential capacity of phragmites ecotypes in remediation of inorganic contaminants in coastal ecosystems: Implications for climate change - Noreen Akhter; Muhammad Aqeel; Shazia; Muhammad Kashif Irshad; Muhammad Muslim Shehnaz; Sang Soo Lee; Ali Noman; Asad Syed; A. Bokhari; Ali H. Bahkali; Ling Shing Wong (Environmental Research, 2024)

Spectrophotometric, microscopic, crystallographic and X-ray based optimization and biological applications of Olea paniculata leaf extract mediated silver nanoparticles - Muhammad Faran Akhtar; Muhammad Irshad; Shaukat Ali; Muhammad Summer; Muhammad Jawad; Muhammad Faizan Akhter; Muhammad Adeel Farooq; Ghulam Asghar (South African Journal of Botany, 2024)

UV-spectrophotometric Optimization of Temperature, pH, Concentration and Time for Eucalyptus Globulus Capped Silver Nanoparticles Synthesis, their Characterization and Evaluation of Biological Applications - Ansar Aziz Subhani; Muhammad Irshad; Shaukat Ali; Muhammad Jawad; Muhammad Faran Akhtar; Muhammad Summer (Journal of Fluorescence, 2024)

Corrigendum to “Evaluation of nanoceria on cadmium uptake in Triticum aestivum (L.) and its implications for dietary health risk” [Chemosphere 341 November (2023) 140115] - Arwa Abdulkreem AL-Huqail; Suliman Mohammed Suliman Alghanem; Zahid Khorshid Abbas; Nora M. Al Aboud; Nasir Masood; Muhammad Atif Irshad; Tahir Abbas; Amany H.A. Abeed; Doaa Bahaa Eldin Darwish (Chemosphere, 2024)

Influence of biochar produced from negative pressure-induced carbonization on transformation of potentially toxic metal(loid)s concerning plant physiological characteristics in industrially contaminated soil - Ayesha Imtiyaz Cheema; Guijian Liu; Balal Yousaf; Aniqa Ashraf; Muyuan Lu; Samina Irshad; Krzysztof Pikon; Mehr Ahmed Mujtaba Munir; Muhammad Saqib Rashid (Journal of Environmental Management, 2023)

Retention of methyl iodide on metal and TEDA impregnated activated carbon using indigenously developed setup - Talhat Yaqoob; Masroor Ahmad; Yasir Faiz; Farman Ali; Amjad Farooq; Faisal Faiz; Attaullah Shah; Muhammad Asim Irshad; Naseem Irfan; Nisar Ali; Sahid Mehmood (Environmental Research, 2023)

Enhancing solar steam generation in hydrogel evaporator by bio-based microfluidic component - Changyuan Song; Muhammad Sultan Irshad; Zhengtong Li; Junhua Hu; Guosheng Shao; Wentao Liu; Xingtao Xu (Chemical Engineering Journal, 2023)

Biowaste-based sorbents for arsenic removal from aqueous medium and risk assessment - Maham Akhtar Nagra; Natasha Natasha; Irshad Bibi; Tasveer Zahra Tariq; Rabia Naz; Sabah Ansar; Muhammad Shahid; Behzad Murtaza; Muhammad Imran; Muhammad Shafique Khalid; Nasir Masood; Ghulam Mustafa Shah; et al. (Environmental Geochemistry and Health, 2023)

Risk assessment of trace element accumulation in soil and Brassica oleracea after wastewater irrigation - Ali Haider Shah; Muhammad Shahid; Maria Tahir; Natasha Natasha; Irshad Bibi; Tasveer Zahra Tariq; Sana Khalid; Muhammad Nadeem; Ghulam Abbas; Muhammad Farhan Saeed; Sabah Ansar; Camille Dumat (Environmental Geochemistry and Health, 2023)

Evaluation of nanoceria on cadmium uptake in Triticum aestivum (L.) and its implications for dietary health risk - Arwa Abdulkreem AL-Huqail; Suliman Mohammed Suliman Alghanem; Zahid Khorshid Abbas; Nora M. Al Aboud; Nasir Masood; Muhammad Atif Irshad; Tahir Abbas; Amany H.A. Abeed; Doaa Bahaa Eldin Darwish (Chemosphere, 2023)

Risk assessment of toxic and hazardous metals in paddy agroecosystem by biochar-for bio-membrane applications - Muhammad Kashif Irshad; Sihang Zhu; Wasim Javed; Jong Cheol Lee; Abid Mahmood; Sang Soo Lee; Shang Jianying; Gadah Albasher; Atif Ali (Chemosphere, 2023)

Thin-film nanocomposite membranes for efficient removal of emerging pharmaceutical organic contaminants from water - Asif Matin; Nadeem Baig; Deepak Anand; Irshad Ahmad; Muhammad Sajid; Muhammad Saqib Nawaz (Environmental Research, 2023)

Exploring perovskite oxide for advancing salt-resistant photothermal membranes and reliable thermoelectric generators - Naila Arshad; Muhammad Sultan Irshad; Muneerah Alomar; Jinming Guo; M. Sohail Asghar; Naveed Mushtaq; M.A.K. Yousaf; Uzma Ghazanfar; Matiullah Shah; Xianbao Wang; Yabin Hao; Lien Thi Do; et al. (Chemical Engineering Journal, 2023)

Unraveling the impact of human perturbation on nitrogen cycling in terrestrial ecosystems of lower Himalaya, Pakistan - Tahir Zaman; Saeed Ahmad Asad; Muhammad Irshad; Faridullah; Muhammad Shahzad; Rashid Nazir; Awais Arefeen; Akhtar Iqbal; Farhan Hafeez (Environmental Monitoring and Assessment, 2023)

Green synthesis and characterization of silver and copper nanoparticles and their use as an effective adsorbent for chromium removal and recovery from wastewater - Muhammad Atif Irshad; Sana Sattar; Arwa Abdulkreem AL-Huqail; Suliman M. S. Alghanem; Rab Nawaz; Noor ul Ain; Khalid Mahmud Hussaini; Amany H. A. Abeed (Environmental Science and Pollution Research, 2023)

A new sesquiterpene, prosoterpene, from Prosopis africana (Guill. & Perr.) Taub - Raza Ali; Kayode Muritala Salawu; Muhammad Aamer; Humera Jahan; Priya Tufail; Rimsha Irshad; Farooq-Ahmad Khan; Bilge Sener; M. Iqbal Choudhary; Yan Wang (Natural Product Research, 2023)

Effect of green synthesized cerium oxide nanoparticles on fungal disease of wheat plants: A field study - Modhi O. Alotaibi; Nahaa M. Alotaibi; Adel M. Ghoneim; Noor ul Ain; Muhammad Atif Irshad; Rab Nawaz; Tahir Abbas; Amjad Abbas; Muhammad Rizwan; Shafaqat Ali (Chemosphere, 2023)

In-situ physical and chemical remediation of Cd and Pb contaminated mine soils cultivated with Chinese cabbage: A three-year field study - Se Jin Oh; Muhammad Kashif Irshad; Min Woo Kang; Hyun-Seog Roh; Yukwon Jeon; Sang Soo Lee (Journal of Hazardous Materials, 2023)

The role of environmental regulation and green human capital towards sustainable development: The mediating role of green innovation and industry upgradation - Likun Ni; Sayed Fayaz Ahmad; Talal Obaid Alshammari; Haoshen Liang; Ghadeer Alsanie; Muhammad Irshad; Randah Alyafi-AlZahri; Rima H. BinSaeed; Mohammed Hasan Ali Al-Abyadh; Sahar Moh'd Mahmood Abu Bakir; Ahmad Y.A. Bani Ahmad Ayassrah (Journal of Cleaner Production, 2023)

Recent advances in green hydrogen production, storage and commercial-scale use via catalytic ammonia cracking - Muhammad Asif; Syeda Sidra Bibi; Sheraz Ahmed; Muhammad Irshad; Muhammad Shakir Hussain; Hassan Zeb; Muhammad Kashif Khan; Jaehoon Kim (Chemical Engineering Journal, 2023)

The effect of gibberellic acid on wheat growth and nutrient uptake under combined stress of cerium, zinc and titanium dioxide nanoparticles - Arwa Abdulkreem AL-Huqail; Dikhnah Alshehri; Rab Nawaz; Muhammad Atif Irshad; Azka Iftikhar; Khalid Mahmud Hussaini; Muhammad Rizwan; Suliman M.S. Alghanem; Amany H.A. Abeed (Chemosphere, 2023)

The deteriorating effects of cadmium accumulation on the yield and quality of maize crops - Naila Shah; Muhammad Irshad; Anwar Hussain; Asif Mehmood; Waheed Murad; Muhammad Qadir; Muhammad Awais; Mohib Shah; Naeem Khan (South African Journal of Botany, 2023)

Microplastics in soil differentially interfere with nutritional aspects of chilli peppers - Khadiga Alharbi; Muhammad Aqeel; Noreen Khalid; Atia Nazir; Muhammad Kashif Irshad; Fahad Mohammed Alzuaibr; Haifa AbdulAziz Sakit AlHaithloul; Noreen Akhter; Omar Mahmoud Al-Zoubi; Muhammad Qasim; Khalid M.Al Syaad; Manal Abdullah AlShaqhaa; et al. (South African Journal of Botany, 2023)

Combination of melatonin and plant growth promoting rhizobacteria improved the growth of Spinacia oleracea L. under the arsenic and cadmium stresses - Mahnoor Asif; Rafiq Ahmad; Arshid Pervez; Dunia A. Al Farraj; Mohamed S. Elshikh; Muhammad Shahzad; Usman Irshad; Arshad Mehmood Abbasi (Physiological and Molecular Plant Pathology, 2023)

Evaluating ionic liquids for its potential as eco-friendly solvents for naproxen removal from water sources using COSMO-RS: Computational and experimental validation - Huma Warsi Khan; Mohd Kaif Khan; Muhammad Moniruzzaman; Mohammed K. Al Mesfer; Mohd Danish; Kashif Irshad; Mohammad Yusuf; Hesam Kamyab; Shreshivadasan Chelliapan (Environmental Research, 2023)

Effect of titanium dioxide nanoparticles and co-composted biochar on growth and Cd uptake by wheat plants: A field study - Fu Chen; Yuhang Li; Muhammad Atif Irshad; Afzal Hussain; Rab Nawaz; Muhammad Farooq Qayyum; Jing Ma; Muhammad Zia-ur-Rehman; Muhammad Rizwan; Shafaqat Ali (Environmental Research, 2023)

Assessment of heavy metals and associated oxidative stress in occupationally exposed workers from Bannu and Karak Districts in Pakistan - Kaleem Khan; Muhammad Tariq Rafiq; Aziz-Ur-Rahim Bacha; Iqra Nabi; Muhammad Irshad; Faridullah Faridullah; Muhammad Younas; Muhammad Daud Khan; Rukhsanda Aziz; Muhammad Amin; Awais Arifeen; Sohaib Aslam; et al. (Environmental Geochemistry and Health, 2023)

Spectroscopic fingerprinting, pollution characterization, and health risk assessment of potentially toxic metals from urban particulate matter - Abdul Rehman; Guijian Liu; Balal Yousaf; Samra Ijaz; Samina Irshad; Ayesha Imtiyaz Cheema; Muhammad Umair Riaz; Aniqa Ashraf (Environmental Science and Pollution Research, 2023)

Synthesis, characterization and antifungal potential of titanium dioxide nanoparticles against fungal disease (Ustilago tritici) of wheat (Triticum aestivum L.) - Nadiyah M. Alabdallah; Muhammad Atif Irshad; Muhammad Rizwan; Rab Nawaz; Aqil Inam; Muhammad Mohsin; Iram Khurshid; Hesham F. Alharby; Atif A. Bamagoos; Shafaqat Ali (Environmental Research, 2023)

Reduction in the cadmium (Cd) accumulation and toxicity in pearl millet (Pennisetum glaucum L.) by regulating physio-biochemical and antioxidant defense system via soil and foliar application of melatonin - Samrah Afzal Awan; Imran Khan; Muhammad Rizwan; Muhammad Atif Irshad; Wang Xiaosan; Xinquan Zhang; Linkai Huang (Environmental Pollution, 2023)

Glutathione treatment suppresses the adverse effects of microplastics in rice - Fu Chen; Muhammad Aqeel; Noreen Khalid; Muhammad Kashif Irshad; Fozia Farhat; Atia Nazir; Jing Ma; Muhammad Saeed Akhtar; Gaber E. Eldesoky; Ahmed Muteb Aljuwayid; Ali Noman (Chemosphere, 2023)

Interactive effects of polystyrene microplastics and Pb on growth and phytochemicals in mung bean (Vigna radiata L.) - Fu Chen; Muhammad Aqeel; Noreen Khalid; Atia Nazir; Muhammad Kashif Irshad; Muhammad Usman Akbar; Fahad Mohammed Alzuaibr; Jing Ma; Ali Noman (Journal of Hazardous Materials, 2023)

A review on covalent organic frameworks as adsorbents for organic pollutants - Awais Ali Aslam; Adnan Irshad; Muhammad Shahid Nazir; Muhammad Atif (Journal of Cleaner Production, 2023)

High internal phase-phase change composites for customized thermal management and anti-counterfeiting - Zhuoya Jia; Chao Chen; Youshuang Zhou; Muhammad Sultan Irshad; Qunchao Zhang; Tao Jiang; Dean Shi; Jun You (Chemical Engineering Journal, 2023)

Simulated Grazing (Clipping) Affected Growth and Nutritional Quality of Barley, Rye, and Wheat in an Arid Climate - Irshad Ahmad; Hua Wang; Muhammad Kamran; Khushnuma Ikram; Fujiang Hou (Journal of Plant Growth Regulation, 2023)

Load Frequency Control of Marine Microgrid System Integrated with Renewable Energy Sources - Guoqiang Zhang; Irfan Ahmed Khan; Amil Daraz; Abdul Basit; Muhammad Irshad Khan (Journal of Marine Science and Engineering, 2023)
In seaports, low-carbon energy systems and energy efficiency have become increasingly important as a result of the evolution of environmental and climate change challenges. In order to ensure the continued success of seaports, technological advancements must be introduced to a number of systems, such as seaport vehicles, harbor cranes, and the power sources of berthed ships. Harbor areas might need a microgrid to handle these aspects. Typically, microgrids that substitute conventional generator units with renewable energy sources (RES) suffer from system inertia problems, which adversely affect microgrid frequency stability. A load frequency controller (LFC) based on a novel modified proportional integral derivative with filter (MPIDF) is presented in this paper for enhancing the performance of marine microgrid system (MMS). The serval optimization algorithm (SOA), a recent bio-inspired optimization algorithm, is used to optimize the MPIDF controller coefficients. This controller is tested on a marine microgrid containing a number of RES such as wind turbine generators, sea wave energy, and solar generation. The efficacy of the proposed MPIDF controller is verified with respect to other controllers such as PIDF and PI. Similarly, the proposed meta-heuristic algorithm is validated as compared to other algorithms including particle swarm optimization (PSO), ant colony optimization (ACO), and jellyfish swarm optimization (JSO). This study also evaluates the robustness of the proposed controller to different perturbations in step load, changes in system parameters, and other parameter variations.

Vegetable oils as bio-based precursors for epoxies - Fareeha Marriam; Adnan Irshad; Isra Umer; Muhammad Arslan Asghar; Muhammad Atif (Sustainable Chemistry and Pharmacy, 2023)

Plant-soil-microbe interactions in maintaining ecosystem stability and coordinated turnover under changing environmental conditions - Muhammad Aqeel; Jinzhi Ran; Weigang Hu; Muhammad Kashif Irshad; Longwei Dong; Muhammad Adnan Akram; Gaber E. Eldesoky; Ahmed Muteb Aljuwayid; Lai Fatt Chuah; Jianming Deng (Chemosphere, 2023)

Investigation of ceria-molten carbonate electrolyte, composite anode and its catalytical effect on various carbon fuels in molten carbonate direct coal/carbon fuel cell - Muhammad Ahsan; Peifang Fu; Kang Bie; Muneeb Irshad; Yang Liu; Tianyao Xu (Fuel, 2023)

Effect of freshwater and wastewater irrigation on buildup of toxic elements in soil and maize crop - Muhammad Shahid; Abdullah A. Al-Kahtani; Zeid A. ALOthman; Irshad Bibi; Tasveer Zahra Tariq; Natasha Natasha; Sana Khalid; Nabeel Khan Niazi; Behzad Murtaza (Environmental Monitoring and Assessment, 2023)

Phosphorus extractability from saline and non-saline soils using different extraction methods - Muneeza Mehfooz; Sumera Bibi; Muhammad Irshad; Zahid Hussain; Muhammad Mohiuddin; Ping An (Arabian Journal of Geosciences, 2023)

Antagonistic impact on cadmium stress in alfalfa supplemented with nano-zinc oxide and biochar via upregulating metal detoxification - Hafiz Abdul Kareem; Muhammad Adeel; Muhammad Azeem; Muhammad Arslan Ahmad; Noman Shakoor; Mahmood Ul Hassan; Sana Saleem; Annie Irshad; Junpeng Niu; Zhipeng Guo; Ćupina Branko; Roman Hołubowicz; et al. (Journal of Hazardous Materials, 2023)

An assessment of the efficacy of biochar and zero-valent iron nanoparticles in reducing lead toxicity in wheat (Triticum aestivum L.). - Muhammad Nauman Mahamood; Sihang Zhu; Ali Noman; Abid Mahmood; Sana Ashraf; Muhammad Aqeel; Muhammad Ibrahim; Sobia Ashraf; Rock Keey Liew; Su Shiung Lam; Muhammad Kashif Irshad (Environmental Pollution, 2023)

Highly charged solar evaporator toward sustainable energy transition for in-situ freshwater & power generation - Muhammad Sultan Irshad; Yabin Hao; Naila Arshad; Muneerah Alomar; Liangyou Lin; Xiuqiang Li; Swelm. Wageh; Omar A. Al-Hartomy; Abdullah G. Al-Sehemi; Van-Duong Dao; Hao Wang; Xianbao Wang; et al. (Chemical Engineering Journal, 2023)

The role of various ameliorants on geochemical arsenic distribution and CO2-carbon efflux under paddy soil conditions - Muhammad Mahroz Hussain; Irshad Bibi; Fawad Ali; Zulfiqar Ahmad Saqib; Muhammad Shahid; Nabeel Khan Niazi; Khalid Hussain; Sabry M. Shaheen; Hailong Wang; Qamar Shakil; Jörg Rinklebe (Environmental Geochemistry and Health, 2023)

Understanding the dynamics of capital structure, corporate governance, and corporate social responsibility in high- and low-leveraged US and Chinese firms - Ahmad Nawaz Mahmood; Hafiz Muhammad Arslan; Zahid Irshad Younas; Bushra Komal; Kamran Ali; Muhammad Mubeen (Environmental Science and Pollution Research, 2023)

Application of Nanomaterials for Cadmium Adsorption for Sustainable Treatment of Wastewater: a Review - Muhammad Atif Irshad; Rab Nawaz; Ewa Wojciechowska; Muhammad Mohsin; Nicole Nawrot; Iqra Nasim; Fida Hussain (Water, Air, & Soil Pollution, 2023)

Exploring antibiotic resistance genes, mobile gene elements, and virulence gene factors in an urban freshwater samples using metagenomic analysis - Sohail M. Noman; Muhammad Shafiq; Shabana Bibi; Bharti Mittal; Yumeng Yuan; Mi Zeng; Xin Li; Oluwaseyi Abraham Olawale; Xiaoyang Jiao; Muhammad Irshad (Environmental Science and Pollution Research, 2023)

Assessment of greenhouse gases emissions, global warming potential and net ecosystem economic benefits from wheat field with reduced irrigation and nitrogen management in an arid region of China - Muhammad Kamran; Zhengang Yan; Irshad Ahmad; Qianmin Jia; Muhammad Usman Ghani; Xianjiang Chen; Shenghua Chang; Tengfei Li; Kadambot H.M. Siddique; Shah Fahad; Fujiang Hou (Agriculture, Ecosystems & Environment, 2023)

Urban Heat Island vulnerability mapping using advanced GIS data and tools - Paras Sidiqui; Phillip B Roös; Murray Herron; David S Jones; Emma Duncan; Ali Jalali; Zaheer Allam; Bryan J Roberts; Alexander Schmidt; Muhammad Atiq Ur Rehman Tariq; Ashfaq Ahmed Shah; Nasir Abbas Khan; et al. (Journal of Earth System Science, 2022)

Comparative Assessment of Remediation Potential of Xanthium strumarium Ecotypes in NaCl-Affected Root Zone - Noreen Akhter; Muhammad Aqeel; Muhammad Faisal Maqsood; Saher Nawaz; Muhammad Muslim Shahnaz; Noreen Khalid; Mohammed A. Basahi; Omar Mahmoud Al-Zoubi; Talaat Habeeb; Romina Alina Marc; Muhammad Kashif Irshad; Ali Noman (Water, Air, & Soil Pollution, 2022)

Natural polysaccharide-based biodegradable polymeric platforms for transdermal drug delivery system: a critical analysis - Sobia Noreen; Jin-Xiang Ma; Muhammad Saeed; Fahad Pervaiz; Muhammad Farhan Hanif; Bilal Ahmed; Muhammad Irshad Farooq; Faizan Akram; Muhammad Safdar; Asadullah Madni; Muhammad Naveed; Li Chang-Xing (Drug Delivery and Translational Research, 2022)

Evaluation of unconventional hydrocarbon reserves using petrophysical analysis to characterize the Yageliemu Formation in the Yakela gas condensate field, Tarim Basin, China - Wakeel Hussain; Lin Pan; Xiao Wang; Muhammad Saqlain; Muhammad Ali; Rakhshanda Sadaf; Nafees Ali; Irshad Hussain; Sajid Ali; Mazahir Hussain; Ali Asghar (Arabian Journal of Geosciences, 2022)

Effects of climate change on vegetation and snow cover area in Gilgit Baltistan using MODIS data - Zulqarnain Satti; Muhammad Naveed; Muhammad Shafeeque; Sikandar Ali; Farkhod Abdullaev; Tauseef Muhammad Ashraf; Muhammad Irshad; Lanhai Li (Environmental Science and Pollution Research, 2022)

Neurotoxic effects of environmental contaminants—measurements, mechanistic insight, and environmental relevance - Nadia Afsheen; Sadia Rafique; Hamza Rafeeq; Kanwal Irshad; Asim Hussain; Zille Huma; Vineet Kumar; Muhammad Bilal; Lotfi Aleya; Hafiz M. N. Iqbal (Environmental Science and Pollution Research, 2022)

Review on integrated disease and pest management of field crops - Muneer Abbas; Muhammad Saleem; Dilbar Hussain; Muhammad Ramzan; Muhammad Jawad Saleem; Sohail Abbas; Niaz Hussain; Muhammad Irshad; Khalid Hussain; Ghulam Ghouse; Mudassar Khaliq; Zubeda Parveen (International Journal of Tropical Insect Science, 2022)

Influence of biochar on trace element uptake, toxicity and detoxification in plants and associated health risks: A critical review - Natasha Natasha; Muhammad Shahid; Sana Khalid; Irshad Bibi; Muhammad Asif Naeem; Nabeel Khan Niazi; Filip M. G. Tack; James Anthony Ippolito; Jörg Rinklebe (Critical Reviews in Environmental Science and Technology, 2022)

Pathological effects of graded doses of aflatoxin B1 on the development of the testes in juvenile white leghorn males - Anas Ashraf; Muhammad Kashif Saleemi; Mashkoor Mohsin; Shafia Tehseen Gul; Muhammad Zubair; Faqir Muhammad; Sheraz Ahmed Bhatti; Muhammad Raza Hameed; Muhammad Imran; Hamid Irshad; Iqra Zaheer; Ishtiaq Ahmed; et al. (Environmental Science and Pollution Research, 2022)

Carica papaya ameliorates thrombocytopenia through upregulation of Interleukin-11 and modulation of thrombopoietin in mouse model of carboplatin-induced myelosuppression - Sabeen Irshad; Arham Shabbir; Hina Aslam; Tasleem Akhtar; Muhammad Shahzad (Molecular Biology Reports, 2022)

Arsenic-induced oxidative stress in Brassica oleracea: Multivariate and literature data analyses of physiological parameters, applied levels and plant organ type - Natasha; Muhammad Shahid; Sana Khalid; Irshad Bibi; Samina Khalid; Nasir Masood; Saeed Ahmad Qaisrani; Nabeel Khan Niazi; Camille Dumat (Environmental Geochemistry and Health, 2022)

An improved capacity design procedure incorporating the effect of gap-opening on higher mode responses in rocking wall structures - Muhammad Irshad Qureshi; Pennung Warnitchai; Tahir Mehmood; Sibghat Ullah Khan; Asif Iqbal (Bulletin of Earthquake Engineering, 2022)

RETRACTED ARTICLE: The nexus between urbanization, renewable energy consumption, financial development, and CO2 emissions: evidence from selected Asian countries - Ahsan Anwar; Avik Sinha; Arshian Sharif; Muhammad Siddique; Shoaib Irshad; Waseem Anwar; Summaira Malik (Environment, Development and Sustainability, 2022)

Marble waste site suitability assessment using the GIS-based AHP model - Muhammad Fawad; Farid Ullah; Muhammad Irshad; Wisal Shah; Qaisar Mahmood; Iqbal Ahmad (Environmental Science and Pollution Research, 2022)

A review on sources of heavy metals, their toxicity and removal technique using physico-chemical processes from wastewater - Muhammad Rafique; Syeda Hajra; Muhammad Bilal Tahir; Syed Sajid Ali Gillani; Muneeb Irshad (Environmental Science and Pollution Research, 2022)

Examining the carbon emissions and climate impacts on main agricultural crops production and land use: updated evidence from Pakistan - Abdul Rehman; Hengyun Ma; Ilhan Ozturk; Muhammad Irshad Ahmad (Environmental Science and Pollution Research, 2022)

Implementation of Vaccinomics and In-Silico Approaches to Construct Multimeric Based Vaccine Against Ovarian Cancer - Muhammad Sufyan; Farah Shahid; Faiza Irshad; Anam Javaid; Muhammad Qasim; Usman Ali Ashfaq (International Journal of Peptide Research and Therapeutics, 2021)

The potential of microbes and sulfate in reducing arsenic phytoaccumulation by maize (Zea mays L.) plants - Natasha; Irshad Bibi; Khalid Hussain; Rabia Amen; Israr Masood Ul Hasan; Muhammad Shahid; Safdar Bashir; Nabeel Khan Niazi; Tariq Mehmood; Hafiz Naeem Asghar; Muhammad Farrakh Nawaz; Muhammad Mahroz Hussain; et al. (Environmental Geochemistry and Health, 2021)

Essential oil composition and antibacterial activity of Canarium strictum Roxb. resin - Halima Tahir; Nadeem Muhammad; Azeem Intisar; Muhammad Imran Din; Uzma Qaisar; Muhammad Abdul Qadir; Noor Ul Ain; Zeeshan Ahmad; Pakeeza Aziz; Muhammad Khurram Shahzad; Irshad Hussain (Plant Biosystems, 2021)

Pseudocitrobacter anthropi reduces heavy metal uptake and improves phytohormones and antioxidant system in Glycine max L. - Husna; Anwar Hussain; Mohib Shah; Muhammad Hamayun; Amjad Iqbal; Waheed Murad; Muhammad Irshad; Muhammad Qadir; Ho-Youn Kim (World Journal of Microbiology and Biotechnology, 2021)

Impregnation on activated carbon for removal of chemical warfare agents (CWAs) and radioactive content - Sidra Shaoor Kiani; Amjad Farooq; Masroor Ahmad; Naseem Irfan; Mohsan Nawaz; Muhammad Asim Irshad (Environmental Science and Pollution Research, 2021)

Integrated support vector regressor and hybrid neural network techniques for earthquake prediction along Chaman fault, Baluchistan - Umer Khalil; Bilal Aslam; Zaheer Abbas Kazmi; Ahsen Maqsoom; Muhammad Irshad Qureshi; Sheheryar Azam; Ahsan Nawaz (Arabian Journal of Geosciences, 2021)

Mitochondrial phylogenetic and diversity analysis in Azi-Kheli buffalo - Farhad Ali; Ijaz Ahmad; Muhammad Ijaz Ali; Muhammad Hasnain Riaz; Nadar Khan; Obaid Ullah; Faizul Hassan; Syed Muhammad Suhail; Rajwali Khan; Muhammad Tahir Khan; Irshad Ahmad; Muhammad Tariq Zeb (Tropical Animal Health and Production, 2021)

Geochemical fractionation and spectroscopic fingerprinting for evaluation of the environmental transformation of potentially toxic metal(oid)s in surface–subsurface soils - Samina Irshad; Guijian Liu; Balal Yousaf; Muhammad Ubaid Ali; Rafay Ahmed; Abdul Rehman; Muhammad Saqib Rashid; Yusra Mahfooz (Environmental Geochemistry and Health, 2021)

Availability of iodine from acidified soil after manure amendments - Muhammad Mohiuddin; Qian Yu; Gaoyue Si; Muhammad Irshad; Mohamed Farig; Zahid Hussain; Lei Duan (Arabian Journal of Geosciences, 2021)

Prevalence of contamination of aflatoxin M1 in milk: a retrospective analysis of studies conducted in Pakistan - Muhammad Sajid Hamid Akash; Kanwal Rehman; Kanwal Irshad (Environmental Monitoring and Assessment, 2021)

Exogenous Application of Melatonin Induces Tolerance to Salt Stress by Improving the Photosynthetic Efficiency and Antioxidant Defense System of Maize Seedling - Shakeel Ahmad; Wenwen Cui; Muhammad Kamran; Irshad Ahmad; Xiangping Meng; Xiaorong Wu; Wennan Su; Tehseen Javed; Hamed A. El-Serehy; Zhikuan Jia; Qingfang Han (Journal of Plant Growth Regulation, 2021)

Correction to: Elucidating the distinct interactive impact of cadmium and nickel on growth, photosynthesis, metal-homeostasis, and yield responses of mung bean (Vigna radiata L.) varieties - Muhammad Aqeel; Noreen Khalid; Aasma Tufail; Rana Zaheer Ahmad; Muhammad Salim Akhter; Muhammad Luqman; Muhammad Tariq Javed; Muhammad Kashif Irshad; Saad Alamri; Mohamed Hashem; Ali Noman (Environmental Science and Pollution Research, 2021)

Elucidating the distinct interactive impact of cadmium and nickel on growth, photosynthesis, metal-homeostasis, and yield responses of mung bean (Vigna radiata L.) varieties - Muhammad Aqeel; Noreen Khalid; Aasma Tufail; Rana Zaheer Ahmad; Muhammad Salim Akhter; Muhammad Luqman; Muhammad Tariq Javed; Muhammad Kashif Irshad; Saad Alamri; Mohamed Hashem; Ali Noman (Environmental Science and Pollution Research, 2021)

Correction to: Biomonitoring of Toxic Metals in Feathers of Birds from North-Eastern Pakistan - Bushra Rashid; Muhammad Zubair; Nausheen Irshad; Khawaja Shafique Ahmad; Majid Mahmood; Majid Mahmood Tahir; Khizar Hussain Shah; Aqeela Shaheen (Bulletin of Environmental Contamination and Toxicology, 2021)

Biomonitoring of Toxic Metals in Feathers of Birds from North-Eastern Pakistan - Bushra Aziz; Muhammad Zubair; Nausheen Irshad; Khawaja Shafique Ahmad; Majid Mahmood; Majid Mahmood Tahir; Khizar Hussain Shah; Aqeela Shaheen (Bulletin of Environmental Contamination and Toxicology, 2021)
The current study was designed to determine the concentrations of toxic metals (Ni, Pb and Cr) in feathers of birds collected from four regions of NE Pakistan. Feather samples of birds (House Crow, Common Myna and House Sparrow) were collected from different areas. Atomic absorption spectrophotometer was used to determine the concentration of metals in feathers. Analysis of the data revealed that concentrations of Pb and Cr were significantly different ( p < 0.05) among bird species, whereas no difference ( p > 0.05) was detected among bird species (house crow, common myna and house sparrow) for Ni. A significant difference was found for the concentration of Pb and Ni in all the four studied regions. Whereas, non-significant difference was found in all the studied regions for the concentrating of Cr. It was revealed that there is significant rising concentration of metals (Pb, Cr) in feathers of birds in Azad Kashmir.

Extractability of iodine from soils using different methods in relation to soil properties - Muhammad Mohiuddin; Muhammad Irshad; Mohamed Farig; Muhammad Shahzad (Arabian Journal of Geosciences, 2021)

New insights into the phytochemical composition, enzyme inhibition and antioxidant properties of desert cotton ( Aerva javanica (Bum.f) Shult. -Amaranthaceae) - Hammad Saleem; Gokhan Zengin; Kashif-Ur-Rehman Khan; Irshad Ahmad; Muhammad Waqas; Fawzi M. Mahomoodally; Kannan R.R. Rengasamy; Noorazwani Zainol; Syafiq Asnawi Zainal Abidin; Nafees Ahemad (Natural Product Research, 2021)

Biochemically Triggered Heat and Drought Stress Tolerance in Rice by Proline Application - Sajid Hanif; Muhammad Farrukh Saleem; Muhammad Sarwar; Muhammad Irshad; Abdul Shakoor; Muhammad Ashfaq Wahid; Haroon Zaman Khan (Journal of Plant Growth Regulation, 2021)

Hormonal changes with uniconazole trigger canopy apparent photosynthesis and grain filling in wheat crop in a semi-arid climate - Irshad Ahmad; Muhammad Kamran; Xiangping Meng; Shahzad Ali; Shakeel Ahmad; Zhiqiang Gao; Tiening Liu; Qingfang Han (Protoplasma, 2021)

Impact of better cotton initiative on health cost and pesticide exposure of women cotton pickers in Punjab, Pakistan - Muhammad Asim Yasin; Khuda Bakhsh; Rafaqet Ali; Hafiz Irshad Hussain (Environmental Science and Pollution Research, 2021)

Comparative secondary metabolites profiling and biological activities of aerial, stem and root parts of Salvadora oleoides decne (Salvadoraceae) - Hammad Saleem; Irshad Ahmad; Gokhan Zengin; Fawzi M. Mahomoodally; Kashif-Ur- Rehman Khan; Hafiz Muhammad Ahsan; Syafiq Asnawi Zainal Abidin; Nafees Ahemad (Natural Product Research, 2020)

Assessment of health and ecological risks of heavy metal contamination: a case study of agricultural soils in Thall, Dir-Kohistan - Irshad Ullah; Allah Ditta; Muhammad Imtiaz; Sajid Mehmood; Muhammad Rizwan; Muhammad Shahid Rizwan; Amin Ullah Jan; Iftikhar Ahmad (Environmental Monitoring and Assessment, 2020)

The comparative analysis of essential nutrient fractions in permafrost and different land use systems of Diamer Division, Gilgit-Baltistan - Didar Ahmad; Farhan Hafeez; Muhammad Irshad; Qaisar Mehmood; Adnan Ahmed Tahir; Akhtar Iqbal; Faridullah (Arabian Journal of Geosciences, 2020)

Application of biochar in advanced oxidation processes: supportive, adsorptive, and catalytic role - Faheem; Jiangkun Du; Sang Hoon Kim; Muhammad Azher Hassan; Sana Irshad; Jianguo Bao (Environmental Science and Pollution Research, 2020)

Influence of selected mineral material on the water solubility and leachability of heavy metals from contaminated soil - Muhammad Irshad; Sardar Owais Mukhtar (Arabian Journal of Geosciences, 2020)

Bioaccumulation of ytterbium oxide nanoparticles insinuate oxidative stress, inflammatory, and pathological lesions in ICR mice - Muhammad Adeel; Jin Tingting; Tariq Hussain; Xiao He; Muhammad Arslan Ahmad; Muhammad Kashif Irshad; Noman Shakoor; Peng Zhang; Xie Changjian; Yi Hao; Zhang Zhiyong; Rabia Javed; et al. (Environmental Science and Pollution Research, 2020)

RETRACTED ARTICLE: Matrine alleviates neurobehavioral alterations via modulation of JNK-mediated caspase-3 and BDNF/VEGF signaling in a mouse model of burn injury - Adnan Khan; Bushra Shal; Muhammad Naveed; Bakht Nasir; Nadeem Irshad; Hussain Ali; Salman Khan (Psychopharmacology, 2020)

A novel approach for high-level expression and purification of GST-fused highly thermostable Taq DNA polymerase in Escherichia coli - Rahman Ud Din; Muhammad Ismail Khan; Asad Jan; Shah Anwar Khan; Irshad Ali (Archives of Microbiology, 2020)

Determination of oil contents from eight varieties of olea europaea (Olive) grown in Pakistan - Abdul Khaliq; Syed Muhammad Ali Shah; Muhammad Akram; Naveed Munir; Muhammad Daniyal; Muhammad Irshad; Saeed Ahmad (Natural Product Research, 2020)

Foliar application of melatonin delay leaf senescence in maize by improving the antioxidant defense system and enhancing photosynthetic capacity under semi-arid regions - Shakeel Ahmad; Wennan Su; Muhammad Kamran; Irshad Ahmad; Xiangping Meng; Xiaorong Wu; Tehseen Javed; Qingfang Han (Protoplasma, 2020)

Yucasin and cinnamic acid inhibit IAA and flavonoids biosynthesis minimizing interaction between maize and endophyte Aspergillus nomius - Asif Mehmood; Anwar Hussain; Muhammad Irshad; Muhammad Hamayun; Amjad Iqbal; Abdul Tawab; Naeem Khan (Symbiosis, 2020)

Inorganic fertilization improves quality and biomass of Moringa oleifera L. - Muhammad Farhan Aslam; Shahzad M. A. Basra; Muhammad Bilal Hafeez; Shahbaz Khan; Sohail Irshad; Shahid Iqbal; Muhammad Sohail Saqqid; Muhammad Zubair Akram (Agroforestry Systems, 2020)

Fabrication and Characterization of Thiolated Chitosan Microneedle Patch for Transdermal Delivery of Tacrolimus - Zulcaif Ahmad; Muhammad Imran Khan; Muhammad Irfan Siddique; Hafiz Shoaib Sarwar; Gul Shahnaz; Syed Zajif Hussain; Nadeem Irfan Bukhari; Irshad Hussain; Muhammad Farhan Sohail (AAPS PharmSciTech, 2020)

Efficient Capture of Phosphate and Cadmium Using Biochar with Multifunctional Amino and Carboxylic Moieties: Kinetics and Mechanism - Faheem; Jiangkun Du; Jianguo Bao; Muhammad Azher Hassan; Sana Irshad; Muhammad Afnan Talib; Han Zheng (Water, Air, & Soil Pollution, 2020)

Synthesis and Application of Titanium Dioxide Nanoparticles for Removal of Cadmium from Wastewater: Kinetic and Equilibrium Study - Muhammad Atif Irshad; Muhammad Bilal Shakoor; Shafaqat Ali; Rab Nawaz; Muhammad Rizwan (Water, Air, & Soil Pollution, 2019)

Effects of Plant Growth Regulators on Seed Filling, Endogenous Hormone Contents and Maize Production in Semiarid Regions - Irshad Ahmad; Muhammad Kamran; Xiangping Meng; Shahzad Ali; Bayasgalan Bilegjargal; Tie Cai; Tiening Liu; Qingfang Han (Journal of Plant Growth Regulation, 2019)

Estimating the pollution characteristics and health risks of potentially toxic metal(loid)s in urban-industrial soils in the Indus basin, Pakistan - Samina Irshad; Guijian Liu; Balal Yousaf; Habib Ullah; Muhammad Ubaid Ali; Jörg Rinklebe (Environmental Monitoring and Assessment, 2019)

Probing the effect of various lipids and polymer blends on clopidogrel encapsulated floating microcarriers - Saba Irshad; Ikram Ullah Khan; Syed Haroon Khalid; Sajid Asghar; Muhammad Irfan; Ikrima Khalid; Nadeem Sabir; Adnan Ali; Ahmad Nawaz Khan; Abid Mehmood Yousaf; Talib Hussain; Yasser Shahzad (DARU Journal of Pharmaceutical Sciences, 2019)

An Investigation into the Accumulation of Air Borne Trace Metals in the Lungs of Common Myna Acridotheres tristis and Bank Myna Acridotheres ginginianus Captured from Urban and Semi Urban Areas of Lahore and Pattoki, Pakistan - Nida Irshad; Safdar Sidra; Arshad Javid; Sitara Ashraf; Muhammad Rizwan Ullah; Rafia Zafar (Bulletin of Environmental Contamination and Toxicology, 2019)

Application of Uniconazole Improves Photosynthetic Efficiency of Maize by Enhancing the Antioxidant Defense Mechanism and Delaying Leaf Senescence in Semiarid Regions - Irshad Ahmad; Muhammad Kamran; Wennan Su; Wang Haiqi; Shahzad Ali; Bayasgalan Bilegjargal; Shakeel Ahmad; Tiening Liu; Tie Cai; Qingfang Han (Journal of Plant Growth Regulation, 2019)

Relating iron, zinc, and iodine concentrations of crops to the selected soil properties under field conditions - Bushra Haroon; Sumiya Khan; An Ping; Zahid Hussain; Muhammad Irshad (Arabian Journal of Geosciences, 2019)

Polyphenolic profiling of Ipomoea carnea Jacq. by HPLC-DAD and its implications in oxidative stress and cancer - Muhammad Zafar Irshad Khan; Syeda Saniya Zahra; Madiha Ahmed; Humaira Fatima; Bushra Mirza; Ihsan-ul Haq; Shafi Ullah Khan (Natural Product Research, 2019)

Immunoprotective role of LaSota vaccine under immunosuppressive conditions in chicken challenged with velogenic avian avulavirus-1 - Iqra Rauf; Abdul Wajid; Irshad Hussain; Safa Ather; Muhammad Asad Ali (Tropical Animal Health and Production, 2019)

Investigating the drinking and surface water quality and associated health risks in a semi-arid multi-industrial metropolis (Faisalabad), Pakistan - Yusra Mahfooz; Abdullah Yasar; Muhammad Tayyab Sohail; Amtul Bari Tabinda; Rizwan Rasheed; Samina Irshad; Balal Yousaf (Environmental Science and Pollution Research, 2019)

Long-term changes of a waterbird community over 26 years at a Pakistani Ramsar Site - Imran Khaliq; Muhammad Irshad Arshad; Anwar Hussain Gill; Abdul Aleem Chaudhry; Muhammad Anwer Maan; Muhammad Anwar Iqbal; Muhamad Akbar; Diana E. Bowler (Wetlands Ecology and Management, 2019)

A comprehensive review on environmental transformation of selenium: recent advances and research perspectives - Habib Ullah; Guijian Liu; Balal Yousaf; Muhammad Ubaid Ali; Samina Irshad; Qumber Abbas; Rafay Ahmad (Environmental Geochemistry and Health, 2019)

Chemical characterisation and hepatoprotective potential of Cosmos sulphureus Cav. and Cosmos bipinnatus Cav. - Mohammad Saleem; Hafiz Akbar Ali; Muhammad Furqan Akhtar; Uzma Saleem; Ammara Saleem; Iram Irshad (Natural Product Research, 2019)

Seismic hazard assessment of Afghanistan - Muhammad Waseem; Abdul Lateef; Irshad Ahmad; Sarfraz Khan; Waqas Ahmed (Journal of Seismology, 2019)

In vitro production of IAA by endophytic fungus Aspergillus awamori and its growth promoting activities in Zea mays - Asif Mehmood; Anwar Hussain; Muhammad Irshad; Muhammad Hamayun; Amjad Iqbal; Naeem Khan (Symbiosis, 2019)

Fractionation of heavy metals in contaminated soil after amendment with composted cow manure and poultry litter - Bushra Haroon; Muhammad Irshad; Farhan Hafeez; Arshid Pervez; Faridullah (Arabian Journal of Geosciences, 2019)

Arsenic Level and Risk Assessment of Groundwater in Vehari, Punjab Province, Pakistan - Muhammad Shahid; Muhammad Khalid; Camille Dumat; Sana Khalid; Nabeel Khan Niazi; Muhammad Imran; Irshad Bibi; Iftikhar Ahmad; Hafiz Mohkum Hammad; Riaz Ahmad Tabassum (Exposure and Health, 2018)

Seed filling in maize and hormones crosstalk regulated by exogenous application of uniconazole in semiarid regions - Irshad Ahmad; Muhammad Kamran; Shahzad Ali; Tie Cai; Bayasgalan Bilegjargal; Tiening Liu; Qingfang Han (Environmental Science and Pollution Research, 2018)

Application of paclobutrazol: a strategy for inducing lodging resistance of wheat through mediation of plant height, stem physical strength, and lignin biosynthesis - Muhammad Kamran; Irshad Ahmad; Xiaorong Wu; Tiening Liu; Ruixia Ding; Qingfang Han (Environmental Science and Pollution Research, 2018)

Effect of coal and wood ash on phosphorus immobilization in different textured soils - Muhammad Irshad; Farhan Hafeez; Madiha Naseem; Muhammad Rizwan; Mohammad I. Al-Wabel (Arabian Journal of Geosciences, 2018)

Accumulation of anthocyanin in callus cultures of red-pod okra [Abelmoschus esculentus (L.) Hongjiao] in response to light and nitrogen levels - Muhammad Irshad; Biswojit Debnath; Sangeeta Mitra; Yasir Arafat; Min Li; Yueting Sun; Dongliang Qiu (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Acid Rain Deposition Modulates Photosynthesis, Enzymatic and Non-enzymatic Antioxidant Activities in Tomato - Biswojit Debnath; Muhammad Irshad; Sangeeta Mitra; Min Li; Hafiz Muhammad Rizwan; Shuang Liu; Tenfei Pan; Dongliang Qiu (International Journal of Environmental Research, 2018)

Socio-demographic characters, distribution and transformation of iodine in soil, plant and wheat grains at District Diamer, Gilgit-Baltistan, Pakistan - Faridullah; Didar Ahmad; Hina Shabbir; Toqeer Ahmed; Muhammad Irshad; Arif Alam; Asif Sardar (Environmental Geochemistry and Health, 2018)

In vitro regeneration of Abelmoschus esculentus L. cv. Wufu: Influence of anti-browning additives on phenolic secretion and callus formation frequency in explants - Muhammad Irshad; Bizhu He; Shuang Liu; Sangeeta Mitra; Biswojit Debnath; Min Li; Hafiz Muhammad Rizwan; Dongliang Qiu (Horticulture, Environment, and Biotechnology, 2017)

Arsenic accumulation and physiological attributes of spinach in the presence of amendments: an implication to reduce health risk - Muhammad Shahid; Marina Rafiq; Nabeel Khan Niazi; Camille Dumat; Saliha Shamshad; Sana Khalid; Irshad Bibi (Environmental Science and Pollution Research, 2017)

Temporal changes in trace elements in brown soil and soybean after long-term fertilization - Muhammad Imran Ashraf; Na Li; Xiaori Han; Jinfeng Yang; Yue Wang; Shumao Fan; Muhammad Irshad; Qaisar Mahmood (Arabian Journal of Geosciences, 2017)

Remediation of arsenic-contaminated water using agricultural wastes as biosorbents - Muhammad Bilal Shakoor; Nabeel Khan Niazi; Irshad Bibi; Ghulam Murtaza; Anitha Kunhikrishnan; Balaji Seshadri; Muhammad Shahid; Shafaqat Ali; Nanthi S. Bolan; Yong Sik Ok; Muhammad Abid; Fawad Ali (Critical Reviews in Environmental Science and Technology, 2016)

Alleviation of chromium toxicity by glycinebetaine is related to elevated antioxidant enzymes and suppressed chromium uptake and oxidative stress in wheat (Triticum aestivum L.) - Shafaqat Ali; Aaifa Chaudhary; Muhammad Rizwan; Hafiza Tania Anwar; Muhammad Adrees; Mujahid Farid; Muhammad Kashif Irshad; Tahir Hayat; Shakeel Ahmad Anjum (Environmental Science and Pollution Research, 2015)

The effect of excess copper on growth and physiology of important food crops: a review - Muhammad Adrees; Shafaqat Ali; Muhammad Rizwan; Muhammad Ibrahim; Farhat Abbas; Mujahid Farid; Muhammad Zia-ur-Rehman; Muhammad Kashif Irshad; Saima Aslam Bharwana (Environmental Science and Pollution Research, 2015)

Emergence of genetically variant Hepatitis C virus population in response to increased antiviral drug pressure, Pakistan - Muhammad Ali; Irshad Ur Rehman; Muhammad Idrees (Virus Genes, 2014)

Changes in water-extractability of soil inorganic phosphate induced by chloride and sulfate salts - Zahoor Ahmad; Faridullah; Haytham El-Sharkawi; Muhammad Irshad; Toshimasa Honna; Sadahiro Yamamoto; Ahmed Salim Al-Busaidi (Environmental Science and Pollution Research, 2008)